Case Report: Complicated Meckel Diverticulum Spectrum in Children - Gunadi,; Damayanti, Wahyu; Saputra, Robin Perdana; Ramadhita,; Ibrohim, Ibnu Sina; Lestiono, Andi; Melati, Devy; Permatahati, Winda Intan; Widowati, Titis; Makhmudi, Akhmad (Frontiers in Surgery, 2021)
Background: Meckel diverticulum (MD) is the most common congenital anomaly of the intestines, with an incidence of 2% of the general population. It can present as various clinical features with complications and be life threatening if diagnosis is delayed and treatment late. Case presentation: We report three pediatric cases with complicated MD: one female presented with small bowel obstruction, one male with peritonitis, and one female with severe iron-deficiency anemia, without gross gastrointestinal bleeding nor any ectopic gastric mucosa. All patients underwent exploratory laparotomy, segmental small bowel resection and primary anastomosis. They successfully recovered and were uneventfully discharged on the fourth, seventh and tenth postoperative days, respectively. Conclusions: MD can present with various complication spectrums, including small bowel obstruction, peritonitis and severe iron-deficiency anemia, which may cause difficulty in definitive diagnosis, particularly in children. Segmental small bowel resection and primary anastomosis are effective surgical approaches and show good outcomes for MD patients.